Kerjasama Anti-Perdagangan Narkoba Amerika Serikat dan Kuba Sebagai Isu Keamanan Nasional Pada Era Pemerintahan Donald J. Trump - Esmeralda, Ranisa; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Despite all of the conflicts involving the two countries, in reality, the United States of America has an anti-drug trafficking cooperation with Cuba. This research aims to explain the reason on why the U.S. wants the cooperation. The non-traditional security concept will assist this research in explaining the aforementioned cooperation between the U.S. and Cuba. In this advanced era, drugs have evolved into one of the complex problems that is included in the issues of non-traditional security. As for the countermeasure, the non-traditional security concept believes that transnational approach is the perfect way to do it. Under the government of President Trump, U.S. seemed to be more focused on domestic countermeasures. While Cuba, as the weaker state and has less power, is also threatened by the troubling problems that arises from drugs. Therefore, the cooperation between the two countries is deemed as the perfect way to countermeasure all of the problems spiraling from drugs and to protect the national security of each country.